A buyer-vendor system with untimely delivery costs: Traditional coordination vs. VMI with consignment stock. (April 2021) - Çömez-Dolgan, Nagihan; Moussawi-Haidar, Lama; Jaber, Mohamad Y.
Highlights: Considers untimely deliveries and replenishments policies in a two-level supply chain. Considers VMI-CS and traditional coordination mechanisms. Untimely deliveries increase the buyer's optimal cycle length of the buyer. Coordination reduces cost by up 58 VMI-CS mechanism outperforms traditional coordination. Abstract: This paper investigates the impact of coordinating a two-level supply chain that consists of a single-vendor and a single-buyer in the presence of untimely delivery costs. Specifically, early and late deliveries outside an agreed-upon delivery window are penalized. We investigate the replenishment policies of the vendor and the buyer with and without coordination. We show that untimely deliveries increase the replenishment cycle of the buyer, whether it coordinates with the vendor or not. More importantly, under untimely deliveries, coordination has a noticeable impact on aligning the decisions of both players, which is shown to be much more valuable in decreasing total costs. Implementing a coordinated solution becomes beneficial when the vendor's penalty and holding costs are high, the delivery window is narrow, and the buyer's holding and ordering costs are low. Next, we compare the traditional replenishment coordination mechanism with a vendor-managed-inventory (VMI) mechanism with consignment stock (CS) under untimely deliveries. We compare two coordination mechanisms, VMI-CS and traditional, and show that VMI-CS outperforms the other when the delivery times are random, but not so when the conditions are deterministic.